Antioxidant Effect of Sericin in Brain and Peripheral Tissues of Oxidative Stress Induced Hypercholesterolemic Rats - Deori, Meetali; Devi, Dipali; Kumari, Sima; Hazarika, Ankita; Kalita, Himadri; Sarma, Rahul; Devi, Rajlakshmi (Frontiers in Pharmacology, 2016)
This study evaluated the antioxidant effect of crude sericin extract (CSE) from Antheraea assamenisis (Aa) in high cholesterol fed rats. Investigation was conducted by administering graded oral dose of 0.25 and 0.5 gm/kg body weight (b.w.)/day of CSE for a period of 28 days. Experiments were conducted in 30 rats and were divided into five groups: normal control (NC), high cholesterol fed (HCF), HCF + 0.065 gm/kg b.w./day fenofibrate (FF), HCF + sericin 0.25 gm/kg b.w./day (LSD) and HCF + sericin 0.5 gm/kg b.w./day (HSD). In brain, heart, liver, serum and kidney homogenates nitric oxide (NO), thiobarbituric acid reactive substances (TBARS), protein carbonyl content (PCC), superoxide dismutase (SOD), reduced glutathione (GSH) was measured. LSD treatment prevented the alterations in GSH and PCC levels in hypercholesterolemic (HyC) brain tissue homogenates of rats. CSE lowers the serum total cholesterol level in HyC rats by promoting fecal cholesterol (FC) excretion. CSE increases FC level by promoting inhibition of cholesterol absorption in intestine. The endogenous antioxidant reduced significantly and the oxidative stress (OS) marker TBARS level increases significantly in the peripheral tissue of HCF rats. However, the administration of LSD and HSD exhibited a good antioxidant activity by reducing the TBARS level and increasing the endogenous antioxidant in peripheral tissue. In addition, a histological examination revealed loss of normal liver and kidney architecture in cholesterol fed rats which were retained in sericin treated groups. The findings of this study suggested that CSE improves hypercholesterolemia in rats fed a HyC diet. Clinical relevance of this effect of CSE seems worthy of further studies.